WIND ENERGY ASSESSMENT FOR THE CAPITAL CITY OF JORDAN, AMMAN - Al-Ghriybah, Mohanad; Zulkafli, Mohd Fadhli; Didane, Djamal Hissein; Mohd, Sofian (Journal of Applied Engineering Science, 2019)
In this study, the meteorological statistics recorded of seven-year wind speed data of the capital city of Jordan, Amman at height 10 m is utilized to assess the potential of wind energy. Also, statistical assessment of wind characteristics is evaluated by the two-parameter Weibull function. Monthly and annual wind speed variation is also analyzed. The study shows that Amman city is more suitable for small-scale wind turbine farms with the current wind speeds. The values of the shape parameter, and scale parameter show a various ranges between (1-1.5) and (1.5 m/s - 3.5 m/s), respectively. It was also noticed that the annual mean wind speed is between 2.2 and 3.02 m/s. Results also showed that the highest wind power density is in June whereas the lowest is in October. In wind direction estimation, it was found that most of wind direction for the seven-years is between the southwest and the northwest, i.e. (135°-215°).